Development Of Financial Services And Application Of Its Experience To The National Economy - Khaidarova Niginahon Shukhrat kizi (Zien Journals, 2023)
The article discusses the opinion of researchers in the field of financial technology and services, provides the stages of development of financial technology, experience and practice in the development of fintech in developed countries. Factors stimulating their development and obstacles hindering the development of fintech have been identified. Considerable space is devoted to the prospects for their use, as well as to an analysis of the problems that need to be solved in order to remove obstacles to their wider distribution in the domestic economy
Keywords: financial market; financial technologies; financial services